Designing and validating a digital leadership model in the education system: A case study with a mixed approach - Mollazehi , Mostafa; Salajegheh, Sanjar; Firooz Abadi , Amaneh; Shokooh , Zahra (Social Determinants of Health, 2022)
Background: This research aimed to design and validates a digital leadership model in the education system. Methods: This research was a case study with a mixed qualitative-quantitative approach. The statistical population in the qualitative section was 23 experts in education organization, and in the quantitative section, it was 400 education organization employees in Sistan and Baluchestan province. After semi-structured interviews and qualitative content analysis in MAXQDA software, interview coding was done and primary and secondary categories of the research were identified. The causal relationships between categories were identified by structural-interpretive modeling method and MICMAC software and the model was validated by using the partial least squares technique and SMART PLS software. Results: A total of 39 secondary categories were categorized into 7 primary concepts including leadership, technological infrastructure, governance structure, strategy development, policy-making, human resource management and digital culture. It was found that governance structure and digital technology infrastructure, as the underlying variables of digital leadership model, directly affects "digital strategy formulation" and digital strategy affects "human resource management" and "digital policymaking". "Digital culture" can also be institutionalized in the organization through digital policymaking and human resource management, and finally "digital leadership" can be achieved. Conclusion: The present study results can be used by relevant managers in today's dynamic environments that pursue the establishment of digital leadership model in the Iran’s education system, especially in Sistan and Baluchestan province.